Institutional rivalry and organizational challenges in agriculture administration: The case of the agricultural planning department and the PMA secretariat in Uganda - Pasipanodya, Dennys (International Food Policy Research Institute, 2011)
The Plan for Modernisation of Agriculture (PMA) Secretariat has played an important and vital role in the design and delivery of agriculture policy and planning services in Uganda since 2000. Originally established as a mechanism for cross- and inter-sectoral coordination on the implementation of agriculture development policy under the PMA initiative, the PMA Secretariat has evolved to become the main instrument for public agriculture policy and planning in the country. While attracting praise from some elements of the agriculture sector, the PMA also has attracted considerable criticism from other quarters for its overlapping responsibilities with the Agricultural Planning Department of the Ministry of Agriculture, Animal Industry and Fisheries (MAAIF).